L'art moderne et contemporain : peinture, sculpture, photographie, graphisme, nouveaux médias. - Lemoine, Serge (Paris : Larousse Paris, 2006)
Abramovic, Marina ; Acconci, Vito ; Agam, Yaacov ; Albers, Josef ; Andre, Carl ; Appel, Karel ; Arman ; Armleder, John ; Arp, Hans (Jean) ; Atget, Eugène ; Aublet, Félix ; Bacon, Francis ; Baertling, Olle ; Baldessari, John ; Balla, Giacomo ; Barney, Matthew ; Baselitz, Georg ; Bauchant, André ; Baumeister, Willi ; Becher, Bernd & Hilla ; Beckmann, Max ; van den Berghe, Frits ; Bernhard, Lucian ; Beuys, Joseph ; Bidlo, Mike ; Bill, Max ; Bischof, Werner ; Bissière, Roger ; Blake, Peter ; Boccioni, Umberto ; Boltanski, Christian ; Bomberg, David ; Bombois, Camille ; Bonnard, Pierre ; Bourdelle, Emile-Antoine ; Brancusi, Constantin ; Braque, Georges ; Breker, Arno ; Brodowitsch, Alexei ; Broodthaers, Marcel ; Brus, Günter ; Calder, Alexander ; Caro, Anthony ; Carrà, Carlo ; Cartier-Bresson, Henri ; Cassandre, A.M. ; César ; Cézanne, Paul ; De Chirico, Giorgio ; Clemente, Francesco ; Close, Chuck ; Colombo, Gianni ; Cornell, Joseph ; Corner, Philipp ; Cragg, Tony (Anthony) ; Crali, Tullio ; Dali, Salvador ; Delaunay, Robert ; Delaunay, Sonia ; Denis, Maurice ; Derain, André ; Dezeuze, Daniel ; Dibbets, Jan ; Dix, Otto ; van Doesburg, Theo ; van Dongen, Kees ; Dubuffet, Jean ; Duchamp, Marcel ; Dumas, Marlene ; Eliasson, Olafur ; Ernst, Max ; Estes, Richard ; Etienne-Martin ; Evans, Walker ; Fautrier, Jean ; Federle, Helmut ; Feininger, Lyonel ; Riverhead (New York) ; Fontana, Lucio ; Fougeron, André ; Francis, Sam ; Freud, Lucian ; Fritsch, Katharina ; Gabo, Naum ; Gac, Jean Le ; Gauguin, Paul ; Giacometti, Alberto ; Gilbert & George ; Gober, Robert ; Gorin, Jean ; GRAV ; Greenberg, Clement ; Greiman, April ; Grosz, George ; Hamilton, Richard ; Hanson, Duane ; Hantaï, Simon ; Hartung, Hans ; Hatoum, Mona ; Hausmann, Raoul ; Heartfield, John ; etc.
boek